Tubular composite body made of quartz glass and method for production and use thereof
Patent Information
- Application Number
- JP2024124398
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-08
- Filing Date
- 2024-07-31
- Publication Date
- 2025-02-26
Smart Images

Figure 2025026828000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite body made of quartz glass, in particular a tubular composite body made of quartz glass, having a length of at least 1000 mm, having a green wall and an inside diameter of at least 250 mm.
[0002] The present invention also relates to a method for producing a tubular quartz glass composite, in particular for producing a tubular quartz glass composite in an external deposition process, comprising the steps of: (a) providing a sub-straight tube having a through opening extending coaxially with and continuous with a longitudinal axis of the sub-straight tube, a sub-straight tube outer diameter, a sub-straight tube inner diameter, a sub-straight tube wall thickness, a sub-straight tube outer surface, and a sub-straight tube inner surface; (b) rotating the substrate tube about a rotation axis extending coaxially or parallel to a longitudinal axis of the substrate tube; (c) depositing SiO 2 on the outer surface of the substrate tube by at least one deposition burner; 2 The substrate tube and SiO 2 forming a composite from the soot body; (d) sintering the composite by heating at a sintering temperature to form the tubular quartz glass composite. The present invention also relates to a method comprising the steps of:
[0003] Components made of quartz glass in the form of preforms, tubes, rods, flanges, plates, rings, reactors, crucibles, etc. are used in semiconductor production and in the manufacture of optical fibers. Such components are often produced by thermal shaping and / or mechanical processing from tubular semi-finished products made of quartz glass. Increased productivity is driving the demand for larger dimensions of such components, which in particular in tubular semi-finished products are associated with larger wall thicknesses and inner diameters.
[0004] To produce tubular semi-finished products from synthesized silicon dioxide, SiO 2CVD methods (Chemical Vapor Deposition) are known, in which particles are deposited on a substrate from the gas phase. The CVD outside deposition method, known by the abbreviation "OVD" (Outside Vapor Deposition), is generally suitable for the production of large volume semi-finished products. In this method, silicon-containing raw materials are converted into SiO 2 The reaction zone is generated by a heat source, and the substrate longitudinal axis and the heat source move back and forth relative to each other. The substrate can be tubular, also referred to here and below as a "substrate tube". The substrate tube can be made of, for example, quartz glass, SiC, SiSiC (reaction sintered silicon infiltrated silicon carbide), Al 2 O 3 or another ceramic material or graphite and is held and rotated about its longitudinal axis by a lathe-like device, also referred to herein as the "substrate tube holder."
[0005] Depending on the temperature during the deposition process, the amount of synthetic SiO deposited on the substrate tube may vary. 2 This layer is still porous and is hereinafter also called "soot layer" or "soot body", or forms a dense layer of more or less transparent quartz glass. In the case of a porous soot layer, this is sintered in a separate step to form more or less transparent quartz glass (the sintering process is also called "vitrification"). From the tubular quartz glass semi-finished product thus produced, components of synthetic quartz glass, for example solid cylinders, hollow cylinders or parts of these components, which can themselves also serve as semi-finished products for the production of other components, can be obtained by mechanical, chemical and / or thermal aftertreatment. [Background technology]
[0006] US8,316,671B2 describes an OVD outside deposition method for producing a hollow cylinder made of quartz glass. A substrate tube made of quartz glass is prepared, and porous SiO 2 A soot layer is deposited on its outer surface. 2The composite of the soot layer is vitrified in such a way that the inside of the substrate tube remains below the deformation temperature. For this purpose, the inner bore of the substrate tube can be cooled by gas or liquid during the vitrification process. The inner wall of the tubular composite of quartz glass produced in this way is formed by the substrate tube and is smooth and no longer needs to be mechanically processed.
[0007] From US 2013 / 115391 A1 a method is known for producing hollow quartz glass cylinders with a large outer diameter, in which a porous soot body made of silicon dioxide soot is deposited on a substrate by the OVD external deposition method. After the substrate is removed, the soot body is sintered to form a hollow cylinder. Rings are cut from quartz glass, which has a low chlorine content and at the same time a low hydroxyl content and therefore a high viscosity. The quartz glass rings are used as so-called "plasma etching rings" for holding semiconductor wafers in plasma etching systems.
[0008] To vitrify the soot body, it is held in the sintering furnace with its longitudinal axis oriented vertically or horizontally. If the longitudinal axis is oriented vertically, the soot body can be vitrified standing on a pedestal. However, there is a risk that the soot body will deform and collapse under its own weight. As a result, a caterpillar-like structure of circumferential pleats is formed, which may not be able to meet the dimensional accuracy requirements. In particular, a certain minimum inner diameter may be exceeded.
[0009] The method known from EP 701975 A2 avoids some of these disadvantages. In this method, a tubular soot body is inserted into a vitrification furnace where it is held in a vertical orientation by a holding device comprising a support rod which extends from above through the internal bore of the soot body and is connected to a support pedestal on which the lower end of the soot body is initially placed. The support rod is made of carbon fiber reinforced carbon (CFC) and is closely wrapped by a gas-permeable, thin-walled jacket tube made of pure graphite. A graphite support ring is embedded in the internal bore of the soot body at a position above the upper end of the jacket tube, protruding inwardly from the soot body wall into the internal bore of the soot body.
[0010] During vitrification, the soot body is moved zone by zone from its upper end through the annular heating element. This causes the soot body to gradually collapse into the graphite jacket tube and to shrink in length, so that in the first sintering stage it stands upright on the support. The position of the graphite support ring embedded in the soot body is selected so that as a result of the increased length reduction in the second sintering stage it is supported by the graphite jacket tube, so that the soot body is held suspended at its upper end. This method is also referred to below as "suspended vitrification". After vitrification, the jacket tube is removed and the internal bore of the resulting quartz glass tube is reworked by drilling, grinding, honing or etching.
[0011] In order to reduce the graphite contact surface, in a variant of this method according to DE 10303290 B3, a sleeve of synthetic quartz glass is provided between the support rod and the soot body to be vitrified, the production of which is very time-consuming and costly and which is or becomes part of the quartz glass tube.
[0012] In the method known from DE 10064730 A, SiO 2The particles are deposited on an elongated substrate tube rotating about its longitudinal axis, the outer diameter of which is stepped over its length. After removal of the stepped substrate tube, a porous hollow cylindrical soot body is obtained, the inner bore of which has a complementary shape corresponding to the outer diameter shape of the substrate tube, i.e. a stepped shoulder. The soot body thus obtained is suspended in a furnace in a vertical orientation for vitrification, the narrowed region of the inner bore being located at the top and a support rod protruding from above into the inner bore engaging under the stepped shoulder. A relatively wide shoulder in the inner bore is necessary for reliable support of the heavy soot body. Technical Problem
[0013] As the quartz glass cylinder becomes larger, the manufacturing process becomes more difficult due to the weight of the soot body to be sintered and the increasing temperature difference between the inside and the outside. With the above-mentioned methods, it is difficult to reliably hold the heavy soot body during vitrification and to reproducibly manufacture a tube from the quartz glass. In particular, rejects at later stages of the procedure, such as when the soot body is vitrified, should be avoided.
[0014] Porous SiO obtained by known sol-gel or pressing methods 2 body etc., SiO 2 Porous SiO not produced by the soot method 2 Similar problems arise when vitrifying other objects made of
[0015] The present invention is therefore based on the object of providing a method for producing such large-volume tubular composites made of quartz glass by an external deposition method, in particular by an OVD external deposition method.
[0016] In particular, the invention is based on the object of providing a method for the reproducible production of tubular composites made of quartz glass with large internal diameters, in particular internal diameters greater than 200 mm and wall thicknesses greater than 25 mm, by external deposition methods, which avoids the abovementioned disadvantages and in particular reduces the risk of rejects.
[0017] The invention is also based on the object of providing a tubular quartz glass composite which is characterized on the one hand by large dimensions, in particular an inner diameter of more than 200 mm, a wall thickness of more than 25 mm and a length of at least 1000 mm, and at the same time by high dimensional stability. Summary of the Invention
[0018] With regard to this method for producing a tubular composite made of quartz glass, the problem is solved by the invention, which begins with the method described above and involves preparing a substrate tube made at least partially of quartz glass of a first quartz glass property, the soot body being made of quartz glass of a second quartz glass property, the first quartz glass property having a material-specific viscosity at the sintering temperature higher than the material-specific viscosity of the second quartz glass property.
[0019] The above method is carried out by using a SiO 2 The porous soot body is produced from synthetic silicon dioxide by an outside deposition method, in particular by an OVD outside deposition method. 2 The soot body may be subjected to a dehydration treatment in an inert gas, a chlorine-containing gas or in vacuum in order to reduce the hydroxyl content of the quartz glass before sintering to form a more or less transparent quartz glass. Sintering (or vitrification) is carried out, for example, under vacuum or in an atmosphere containing helium and / or hydrogen and / or nitrogen.
[0020] The substrate tube is made of SiO2 with a large inner diameter based on the external deposition method. 2 The substrate tube is designed to create a body on its outer surface. The substrate tube may be, for example, up to 4 m long and may have a cylindrical, conical or stepped shape over the entire length or over a portion of the length. The inner contour may be constant or may vary over the substrate tube length.
[0021] After completion of the deposition process, the substrate tube remains in the composite of the substrate tube and the soot body and becomes part of the tubular quartz glass composite to be produced (hereinafter also called "quartz glass composite" or "composite" for short). It is made of quartz glass and preferably has an inner diameter of at least 250 mm. Its wall thickness is preferably in the range of 4 mm to 10 mm and is therefore small in relation to its outer diameter. The wall thickness is usually less than 20% of the outer diameter of the substrate tube. Thus, the substrate tube has, on the one hand, a low weight, which reduces the driving force of the rotational movements and makes it easier to handle and align, and, on the other hand, a low thermal mass, which keeps the heat dissipation and keeps the formation of thermal stresses in the wall low.
[0022] On the other hand, the wall thickness of the substrate tube is large and the SiO 2 It is large enough to support the soot body. Therefore, it is preferable that the wall thickness of the substrate tube is at least 1% of the outer diameter of the substrate tube. S (in mm) can also depend on the substrate tube length. It is beneficial to increase the wall thickness as the substrate tube length increases. Thus, W S Instead, the outer diameter of the substrate tube D S Depending on the substrate tube length (in mm), S Taking into account the additional factor (in mm), it can be set as follows: W S <0.2×(L S / 2,000mm)×D S .
[0023] After completion of the external deposition process and any dehydration treatment of the soot body, sintering (vitrification) of the soot body is performed by bonding the substrate tube and SiO 2 According to step (d), the soot body is sintered as a composite, i.e. connected to a substrate tube. The substrate tube used here is characterized by a high thermal stability, so that it is less soft than the soot body during sintering of the soot body. The thermally more stable substrate tube provides a certain degree of support to the softening soot body so that it obtains or maintains the desired cylindrical shape.
[0024] This involves the use of SiO2 for both the substrate tube and the soot body. 2 This is due to the fact that there is no or little difference in their thermal expansion coefficients since they are made of 100% tungsten and 100% tungsten. The soot body is sintered onto the substrate tube, which ensures a degree of adhesion of the composite and prevents the soot body from coming off the substrate tube during sintering.
[0025] The relatively higher viscosity of the substrate tube is achieved, for example, by the substrate tube consisting of quartz glass having a higher viscosity at the sintering temperature than the synthetic quartz glass of the soot body over at least a portion of its length and / or over at least a portion of its wall thickness. In the simplest and preferred case, the substrate tube consists entirely of quartz glass of the first quartz glass nature, i.e. quartz glass with a higher viscosity. In another, likewise preferred embodiment, the quartz glass of the substrate tube consists of quartz glass with a higher viscosity only over a portion of its length, for example in the portion of its length that is used as a holder in a sintering furnace during sintering of the soot body.
[0026] The sintering temperature is typically in the range of 1200°C to 1450°C. It has proven useful if the common logarithm of the viscosity of the first quartz glass property at a measurement temperature of 1350°C is at least 0.25 log(dPa·s), preferably at least 0.4 log(dPa·s), particularly preferably at least 0.6 log(dPa·s) higher than that of the quartz glass of the second quartz glass property. The difference in viscosity is expressed here as the difference in common logarithm log(dPa·s) of the corresponding viscosity values. A viscosity difference of more than 1 log(dPa·s) at the measurement temperature is usually not required.
[0027] The viscosity of quartz glass can be altered by stiffening its glass network structure, in particular by dopants. Stiffening of the glass network structure can be achieved by oxygen deficiency centers (also known as "ODC centers" (Oxygen Deficiency Centers)). Nitrogen, titanium oxide and aluminum oxide are suitable dopants for increasing the viscosity of quartz glass. In this respect, according to a preferred method, the quartz glass of the first quartz glass nature has an aluminum oxide content of at least 5 ppm by weight, preferably at least 10 ppm by weight, higher than the aluminum oxide content of the quartz glass of the second quartz glass nature. Thus, with the aim of increasing the viscosity, aluminum oxide can be added to quartz glass designed for components intended to be used at high temperatures and to have a certain degree of temperature stability. The viscosity of the synthesized quartz glass can also be increased in this way.
[0028] Naturally occurring quartz glass raw materials often contain a certain proportion of aluminum oxide. In this regard, the quartz glass of the first quartz glass property is preferably melted from a naturally occurring raw material. The cost of producing a substrate tube from natural quartz glass is relatively low. For example, such a substrate tube can be produced cost-effectively using known crucible drawing methods.
[0029] The quartz glass of the second quartz glass nature is, for example, a synthetic quartz glass which does not contain a significant proportion of aluminium oxide or has a low proportion of aluminium oxide of less than 1 ppm by weight, preferably less than 0.5 ppm by weight, and which is of high purity.
[0030] In contrast, the quartz glass of the first quartz glass property preferably contains at least 5 ppm by weight, preferably at least 10 ppm by weight, although an aluminium oxide content of more than 100 ppm by weight is generally not preferred.
[0031] The viscosity of the quartz glass can also be changed by hydroxyl groups, which can reduce the viscosity of the quartz glass. In this respect, according to a preferred method, the quartz glass of the first quartz glass property has a hydroxyl group content of less than 30 ppm by weight, preferably a hydroxyl group content of less than 20 ppm by weight.
[0032] Quartz glass quality produced from natural raw materials can have a hydroxyl content of less than 30 ppm by weight, for example by melting the raw materials in an electrically heated furnace or using a hydrogen-free plasma. SiO 2 The hydroxyl content of the quartz glass synthesized in the soot route can be adjusted within a wide range by drying the soot body before vitrification. As a result of this drying process, a low hydroxyl content in the range of a few ppm by weight, characterized by a relatively low viscosity, is also obtained in the synthesized quartz glass. In some cases, if the viscosity of the quartz glass of the soot body to be applied thereto is relatively low, the synthetic quartz glass with a low hydroxyl content is suitable as a substrate tube material.
[0033] In a preferred method, a substrate tube is used having a wall thickness in the range of 1.5 mm to 10 mm, preferably in the range of 4 to 8 mm.
[0034] The wall thickness is as large as necessary to ensure the desired thermal stability, while being as small as possible since the substrate tube material is typically removed during further processing of the fused silica composite.
[0035] This substrate tube and SiO 2 The quartz glass composite obtained after vitrification of the composite consisting of the soot layer and the soot body has an inner wall region made of a first quality of quartz glass derived from the original substrate tube, and an outer wall region made of a second quality of quartz glass derived from the original soot body, the thickness of the outer wall region being a function of the wall thickness of the soot body and the soot density.
[0036] The soot density is typically in the range of 25-33% of the density of quartz glass. In this respect, the soot body obtained by the external deposition method is preferably substantially cylindrical and preferably has a wall thickness such that after sintering of the composite a glass layer is obtained with a layer thickness in the range of 25 mm to 100 mm, preferably in the range of 30 mm to 60 mm.
[0037] The above mentioned technical problem is solved by the present invention by starting with a tubular quartz glass composite as described above, the green wall having an inner wall region and an outer wall region, said inner wall region at least partially consisting of quartz glass of a first quartz glass property and said outer wall region consisting of quartz glass of a second quartz glass property, the viscosity of said first quartz glass property being higher than the viscosity of said second quartz glass property at a measuring temperature of 1350°C.
[0038] According to the invention, a tubular quartz glass composite can be produced using the method described above. The outer wall region of the quartz glass composite is made of original SiO 2 It may be formed from quartz glass obtained by sintering a soot body, with the inner wall region being formed from the quartz glass of the original substrate tube.
[0039] Since both the inner and outer wall regions are made of quartz glass, there is no or little difference in their thermal expansion coefficients. During pre-sintering, the soot body is sintered onto the substrate tube, which ensures a certain degree of adhesion of the composite.
[0040] The relatively higher viscosity of the inner wall region is achieved, for example, by the inner wall region consisting of quartz glass which, at least over a portion of its length and / or at least over a thickness region, has a higher viscosity at the measuring temperature of 1350° C. than the synthetic quartz glass of the outer wall region.
[0041] It has proven useful that the common logarithm of the viscosity of the first quartz glass property at a measuring temperature of 1350° C. is at least 0.25 log(dPa·s), preferably at least 0.4 log(dPa·s), particularly preferably at least 0.6 log(dPa·s) higher than that of the quartz glass of the second quartz glass property. The viscosity difference is expressed here as the difference in common logarithm log(dPa·s) of the corresponding viscosity values. A viscosity difference of more than 1 log(dPa·s) at the measuring temperature is usually not required.
[0042] The inner wall region may contain retaining elements that allow for suspension vitrification to form a quartz glass composite during a prior sintering process. In a preferred embodiment, the quartz glass of the inner wall region consists of a more viscous quartz glass only over a portion of its length, for example in the portion of its length where the retaining elements are located.
[0043] In the simplest and particularly preferred case, the inner wall region consists entirely of quartz glass of the first quartz glass nature, ie quartz glass with a higher viscosity.
[0044] The viscosity of quartz glass can be modified by stiffening its glass network structure, especially by dopants. Stiffening of the glass network structure can be achieved by oxygen deficiency centers (also known as "ODC centers"). Nitrogen, titanium oxide and aluminum oxide are suitable dopants to increase the viscosity of quartz glass.
[0045] In this respect, according to a preferred embodiment of the composite, the quartz glass of the first quartz glass nature has an aluminum oxide content at least 5 ppm by weight, preferably at least 10 ppm by weight, higher than the aluminum oxide content of the quartz glass of the second quartz glass nature. Thus, aluminum oxide can be added to quartz glasses designed for components intended to be used at high temperatures and to have a certain degree of temperature stability, with the aim of increasing the viscosity. The viscosity of the synthesized quartz glass can also be increased in this way.
[0046] Naturally occurring quartz glass raw materials often contain a certain proportion of aluminum oxide. In this regard, the quartz glass of the first quartz glass nature is preferably melted from naturally occurring raw materials. The costs of producing natural quartz glass are relatively low.
[0047] The quartz glass of the second quartz glass nature is, for example, a synthetic quartz glass which does not contain a significant proportion of aluminium oxide or has a low proportion of aluminium oxide of less than 1 ppm by weight, preferably less than 0.5 ppm by weight, and which is of high purity.
[0048] In contrast, the quartz glass of the first quartz glass property preferably contains at least 5 ppm by weight, preferably at least 10 ppm by weight, although an aluminium oxide content of more than 100 ppm by weight is generally not preferred.
[0049] The viscosity of the quartz glass can also be changed by hydroxyl groups, which can reduce the viscosity of the quartz glass. In this respect, according to a preferred embodiment of the composite, the quartz glass of the first quartz glass property has a hydroxyl group content of less than 30 ppm by weight, preferably a hydroxyl group content of less than 20 ppm by weight.
[0050] A hydroxyl content of less than 30 ppm by weight can be obtained, for example, by quartz glass quality made from natural raw materials, the raw materials being melted in an electrically heated furnace or using a hydrogen-free plasma. 2 The hydroxyl content of the quartz glass synthesized in the soot route can be adjusted within a wide range by drying the soot body before vitrification. As a result of this drying process, a low hydroxyl content in the range of a few ppm by weight, characterized by a relatively low viscosity, is also obtained in the synthesized quartz glass. In some cases, if the viscosity of the quartz glass of the applied soot body is relatively low, the synthetic quartz glass with a low hydroxyl content is suitable as a substrate tube material.
[0051] In a preferred composite embodiment, the inner wall region made of the first quality quartz glass has a wall thickness in the range 1.5 mm to 10 mm, preferably in the range 4 to 8 mm.
[0052] The wall thickness is as large as necessary to ensure the desired thermal stability, while being as small as possible since the first nature quartz glass is usually removed during further processing of the composite.
[0053] In a preferred embodiment of the composite, the outer wall region has a wall thickness in the range of 25 mm to 100 mm, preferably in the range of 30 mm to 60 mm.
[0054] By removing the inner wall regions, for example by drilling, milling or etching, hollow quartz glass cylinders are produced from the quartz glass composite, which are used to manufacture etching rings for single-wafer plasma etching chambers or pressure vessels for use in the chemical industry.
[0055] The etching ring or pressure vessel has a given target inner diameter. For the manufacture of the etching ring or pressure vessel, a composite body is preferably used having an outer wall region with an inner diameter at least 1 mm smaller than the target inner diameter. The target inner diameter is set here by excluding the entire inner wall region and a margin in the outer wall region, the margin being 1 mm or more.
[0056] [Definition and measurement methods] The individual terms in the above description are further defined below. The definitions are part of the description of the present invention. For terms and measurement means not specifically defined in the specification, the interpretation given by the International Telecommunication Union (ITU) applies. In case of any discrepancy between the definitions below and the remainder of the specification, the description in the specification shall prevail.
[0057] [Tubular composite made of quartz glass] The result of the deposition method is a substrate tube made of quartz glass and SiO 2The tubular composite is a tubular composite consisting of a soot body and a substrate tube. The substrate tube limits the internal porosity of the composite. Sintering (vitrification) of the soot body results in a tubular composite consisting of quartz glass. The substrate tube is then removed from the quartz glass composite, resulting in a quartz glass hollow cylinder. The substrate tube is removed, for example, by drilling out. Further mechanical, thermal or chemical processes are used to produce quartz glass parts from the quartz glass hollow cylinder. Further mechanical processes include drilling, cutting, cutting, milling, grinding and polishing of the inner and outer contours. Further thermal processes include thermal drying, sintering, vitrification, melting, shaping and tempering. Further chemical processes include doping and etching. The quartz glass parts are ready-to-use quartz glass products or semi-finished products therefor, for example quartz glass hollow cylinders for producing pressure vessels or quartz glass rings for producing holding rings for wafers.
[0058] [Quartz glass / synthetic quartz glass] Here, silica glass is SiO 2 This refers to glasses with a content of at least 87% by weight of undoped (SiO 2 content=100%) or containing dopants such as fluorine, chlorine, nitrogen, carbon, or oxides of boron, germanium, rare earth metals, aluminum, or titanium.
[0059] Silica glass is, for example, a naturally occurring SiO 2 It can be a melt of raw materials (natural quartz glass), synthesized (synthetic quartz glass), or consist of a mixture of these quartz glass types.
[0060] [Sintering / vitrification] "Sintering" or "vitrification" as used herein refers to a process in which a porous silicon dioxide soot body is treated at high temperatures in a furnace. Sintering / vitrification can be carried out in an inert gas, hydrogen and / or helium containing atmosphere, or under vacuum.
[0061] [vacuum] Vitrification of the composite can be carried out under "vacuum". Negative pressure is indicated as absolute gas pressure. Vacuum means an absolute gas pressure of less than 50 mbar.
[0062] [Substraight pipe outer diameter / Substraight pipe inner diameter] The substrate tube cross-section may have a circular or out-of-round outer contour. If the outer contour deviates from round, the local "outer diameter value" is given by the (smallest) circumferential diameter.
[0063] Substrate tube cross sections may have a circular or out-of-round inner contour. If the inner contour deviates from round, the local "inner diameter value" is given by the diameter of the (largest) inscribed circle.
[0064] In a longitudinal section of the substrate tube, the local values of the outer diameter may or may not be constant over the entire length of the substrate tube. If the outer diameter value is constant, the substrate tube is cylindrical when viewed from the outside. If the outer diameter value is not constant, the outer diameter value may vary over the entire length or over partial lengths. The outer contour may vary, for example, continuously or gradually. In this case, the outer diameter is the result of an average of the local outer diameter values over the entire length.
[0065] In a longitudinal section of the substrate tube, the local value of the inner diameter may or may not be constant over the entire length of the substrate tube. If the inner diameter value is constant, the through opening of the substrate tube is cylindrical. If the inner diameter value is not constant, the inner diameter value may vary over the entire length or over a partial length. The inner contour may vary, for example, continuously or gradually. In this case, the inner diameter is the result of an average of the local inner diameter values over the entire length.
[0066] [viscosity] The "viscosity" of quartz glass is measured using a beam bending viscometer. The beam bending viscometer is 8 ~10 15The viscosity range covered is from 8 log(dPa·s) to 15 log dPa·s in logarithmic units. The measurement setup comprises a heatable three-point bending device with a measurement beam made of quartz glass to be measured (beam / strip: length 50 mm, height 3 mm, width 5 mm). The measured quantity is the bending speed at each temperature.
[0067] Instead of exponential notation, viscosity values are often specified using their common logarithm, of the form log(dPa·s).
[0068] [Softening temperature] Glasses cannot be assigned a specific softening temperature, but a softening temperature range. To determine the temperature values, reference is made here to the measurement according to DIN ISO 7884 (1998), according to which the softening temperature is determined when the viscosity of the glass is 10 7.6 The softening temperature of undoped quartz glass is defined as the temperature at which the melting point reaches 7.6 log(dPa·s). For the softening temperature of undoped quartz glass, temperature values in the range of 1600°C to 1730°C are given in the literature.
[0069] The invention will now be explained in more detail with reference to embodiments and patent drawings, the individual figures of which show the following schematic diagrams: [Brief description of the drawings]
[0070] [Figure 1] 1 is a longitudinal sectional view showing an apparatus for manufacturing a composite body consisting of a substrate tube and a soot body in a first embodiment of a substrate tube holder. FIG. [Diagram 2] FIG. 2 is a longitudinal sectional view showing a partial cutaway of an apparatus for producing a composite consisting of a substrate tube and a soot body in a second embodiment of a substrate tube holder. [Diagram 3] FIG. 3 is an enlarged view of a cutout of the substrate tube holder of FIG. 2. [Figure 4] FIG. 1 illustrates components of a zone sintering furnace used for vitrification of composites. [Diagram 5]FIG. 1 shows the vitrification of standing composites using a zone sintering furnace. [Figure 6] 11A to 11C are diagrams showing a process for producing a first embodiment of a holding end on a substrate tube. [Figure 7] 13A-13C show further steps of creating a holding end on a substrate tube. [Figure 8] FIG. 13 shows the vitrification of a partially suspended composite with a first embodiment of a holding end of a substrate tube in a zone sintering furnace. [Figure 9] 13A to 13C are diagrams showing a process for producing a second embodiment of a holding end on a substrate tube. [Figure 10] 13A-13C show further steps of creating a holding end on a substrate tube. [Figure 11] FIG. 13 shows an embodiment of a substrate tube having a retaining end created prior to the external deposition process in the form of a taper in the inner diameter. [Figure 12] 12 shows the substrate tube of FIG. 11 after completion of an external deposition process during vitrification of the composite in the zone sintering furnace of FIG. 4. [Figure 13] FIG. 1 shows a longitudinal cross section of an embodiment of a tubular quartz glass composite according to the present invention.
[0071] In the embodiments described below, different substrate tubes are used, some of whose characteristics are summarized in Table 1.
[0072] Table 1 - Substrate tubes TIFF2025026828000002.tif80169
[0073] "Natural silica glass" refers to the naturally occurring SiO 2 It is melted from the raw material. Substrate tubes made of natural quartz glass are particularly cost-effectively produced using the vertical crucible drawing method. This quartz glass typically contains aluminum oxide in concentrations ranging between 6 ppm and 18 ppm by weight and hydroxyl groups in concentrations less than 50 ppm by weight.
[0074] "Synthetic quartz glass" can be obtained, for example, by flame hydrolysis or oxidation of synthetic silicon compounds, by polycondensation of organosilicon compounds by the so-called sol-gel process, or by hydrolysis and precipitation in liquids of inorganic silicon compounds. The viscosity of synthetic quartz glass depends on its composition and can be in a wide range. However, very generally it can be said that synthetic quartz glass typically has a significantly lower viscosity than natural quartz glass.
[0075] The apparatus shown diagrammatically in FIG. 1 comprises a substrate tube 1 and a SiO 2 The apparatus is used to produce a large volume composite consisting of a substrate body 9 and a soot body 9. The apparatus includes a glass lathe 2 for holding and rotating a substrate tube 1 corresponding to No. 1 in Table 1. The substrate tube 1 has a left end face 1a, a right end face 1b, an outer surface 1c, an inner surface 1d, a horizontal longitudinal axis 1e, and a cylindrical through hole 1f. Adjacent to end face 1a, a SiO 2 There is a free substrate tube section 1g where reduced deposition of soot particles occurs. The free substrate tube section 1g can be formed into a retaining end during vitrification and is described in more detail below with reference to Figures 4, 6-10.
[0076] The glass lathe 2 is represented by two oppositely situated chucks 2a, 2b, of which chuck 2a is sprung as shown by compression spring 2c. Compression spring 2c generates a pressure F which presses the two chucks 2a, 2b against each other as shown by directional arrow 2d.
[0077] A hollow spindle 3a, 3b made of stainless steel is clamped at its proximal end to each of the chucks 2a, 2b. In the ideal case, the rotation axis of the hollow spindle 3a, 3b extends coaxially with the substrate tube longitudinal axis 1e. The hollow spindle 3a, 3b has an outer diameter of 90 mm and an inner diameter of 82 mm.
[0078] The distal ends of the hollow spindles 3a, 3b are pivotally connected to annular pressure plates 4a, 4b made of stainless steel. For this purpose, the distal ends of the hollow spindles 3a, 3b are conically tapered and press against the respective pressure plates 4a, 4b as a result of the force of the springs 2c, whereby the conical ends protrude into the central bore of each annular pressure plate 4a, 4b and abut the inner edge of the central bore.
[0079] The pressure plates 4a, 4b are adjacent to respective buffer disks 5a, 5b made of graphite which in turn are adjacent to the substrate tube end faces 1a and 1b, respectively. The buffer disks 5a, 5b have a central hole whose diameter corresponds to and extends coaxially with the diameter of the pressure plates. The pressure plates 4a, 4b have an outer diameter 10 mm less than the outer diameter of the substrate tube 1. The buffer disks 5a, 5b have an outer diameter extending 40 mm beyond the outer diameter of the substrate tube 1.
[0080] It is made of SiSiC and has a total length of L Z A tubular centering support 6 having an outer diameter of 80 mm at 100 mm extends through the substrate tube through hole 1f and through the central holes of the pressure plates 4a, 4b and the buffer disks 5a, 5b. One end 6a of the centering support 6 has a length L of 500 mm. a 3a and has an end in it, and has a variable movement room B of about 6 mm. a The other end 6b has a length L of 600 mm. b 3b and has an end in it, and also has a variable movement room B of about 6 mm. b The total space for movement within the hollow spindles 3a, 3b of the centering support 6 is B z =B a +B b is therefore 12 mm. The outside diameter of the centering support 6 is constant over its length and is adapted with a clearance fit to the inside diameter of the hollow spindles 3a, 3b so that it can be telescopically moved therein.
[0081] Three centering rings 7a, 7b, 7c made of graphite are placed on the centering support 6. Centering ring 7a is located in the area of the left substrate tube end face 1a, centering ring 7b is located in the area of the right substrate tube end face 1b, and centering ring 7c is located approximately in the center of the substrate tube through hole 1f. The outer diameter of all centering rings 7a, 7b, 7c is adapted with a clearance fit to the inner diameter of the substrate tube and the inner diameter is adapted with a clearance fit to the outer diameter of the centering support.
[0082] The end centering ring 7a, the buffer disk 5a and the pressure disk 4a are loosely connected to each other by a screw 4c. The screw 4c has a thread adjacent to the cylindrical part 4d. In both cases, the thread engages into an inner thread in the pressure disk 4a, so that in the tightened state the cylindrical part 4d abuts tightly against the pressure disk 4a. The length of the cylindrical part 4d is greater than the total thickness of the part stack of the centering ring 7a and the buffer disk 5a, so that the head of the screw 4c does not abut on the centering ring 7a, but a gap remains between the centering ring 7a and the screw head. Furthermore, the through hole for passing the cylindrical part 4d of the buffer disk 5a and the centering ring 7a is larger than the diameter of the cylindrical part 4d, so that the screw 4c can be slightly tilted in the through hole. This loose connection is therefore suitable both to allow thermal changes in length between the parts of the substrate tube holder and to compensate for deviations from the target dimensions, positioning and alignment of the parts. The threads 4c also provide a certain degree of torsional strength between the buffer disk 5a and the pressure disk 4a during the rotational movement of the substrate tube 1, and in this respect act as a driving element for this rotational movement. The same is true for the connection of the centering ring 7b, the buffer disk 5b and the pressure disk 4b. For thermal decoupling, gaps are provided between the centering rings 7a, 7b and the buffer disks 5a, 5b (not visible in the figures).
[0083] SiO 2A number of deposition burners 8 for generating particles are mounted on a common slide 8a, which allows the deposition of the particles along the outer surface 1c of the substrate tube 1 or along the forming SiO 2 as indicated by directional arrow 8b. 2 They can be moved reversibly and laterally along the soot body 9 and can be displaced perpendicularly relative to it.
[0084] 2 and 3, when the same reference numbers are used as in FIG. 1, these indicate the same or equivalent parts or components of the apparatus.
[0085] The apparatus shown diagrammatically in Figure 2 differs from that of Figure 1 essentially with respect to the type and nature of the substrate tube holder and substrate tube 21. Where the same reference numbers as in Figure 1 are used, these indicate the same or equivalent parts or elements of the apparatus as described with reference to Figure 1.
[0086] The substrate tube 21 corresponds to No. 2 in Table 1. In the end region 21a it has a circumferential constriction 26 of the inner diameter. The constriction 26 is produced before the start of the external deposition process, for example by locally softening the substrate tube 21 after clamping it on a glass lathe 2. The constriction 26 is located at a distance of about 80 mm from the front of the substrate tube end face. The inner diameter is 270 mm, except in the region of the constriction 26 where it is 250 mm.
[0087] The hollow spindles 23a, 23b, each clamped at its proximal end in a clamping chuck, are made of stainless steel. In the ideal case, the rotation axes of the hollow spindles 23a, 23b extend coaxially with the substrate pipe longitudinal axis 1e. The hollow spindles 23a, 23b have an outside diameter of 100 mm. A circumferential extension arm 2c is welded to the hollow spindles 23a, 23b in the region of their respective distal ends.
[0088] The pivotable connection between the hollow spindle 23a, 23b and the corresponding pressure plate 24a, 24b is designed here as a floating bearing and preferably comprises a cardboard-conical seat, whereby the distal end of the hollow spindle 23a, 23b each forms a convexly curved seat and has a spherical or radial portion, on which the pressure plate 24a or 24b is movably mounted by means of a concavely curved spherical or radial portion which complements the convexly curved seat.
[0089] FIG. 3 shows an enlarged view of the pivotable connection between the hollow spindles 23a, 23b and the respective pressure plates 24a, 24b. The end centering rings 7a, the buffer disks 5a and the pressure disks 24a form a stack of parts loosely connected to each other by means of screws 24c, which mesh with the threads of the extension arms 23c. The cylindrical part 24d has a length greater than the total thickness of the stack of parts consisting of the centering rings 7a, the buffer disks 5a and the pressure disks 24a. Also, the width of the hole in the stack of parts for receiving the screws 24c is significantly greater than the diameter of the cylindrical part 24d. Due to this, some gaps 25 remain between the screw heads 24e and the centering rings 7a, between the pressure plates 24 and the extension arms 23c, as well as along the cylindrical part 24d, even when the screws 24c are fixedly tightened. The gap 25 ensures that the connection between the hollow spindles 23a, 23b and the corresponding pressure plates 24a, 24b remains pivotable. At the same time, the screw 24c serves as the drive element for the rotational movement of the substrate tube 1.
[0090] An example of the manufacture of a quartz glass composite is described below with reference to FIGS.
[0091] [Soot Deposition Process] Oxygen and hydrogen are supplied as burner gases to the deposition burner 8, and SiCl 4 or a gas stream containing another silicon-containing source is SiO 2 These components are supplied as feed materials to form particles. The SiO2 These SiO 2 The particles are deposited on a substrate tube 1 rotating about a longitudinal axis 1e, and the porous SiO 2 A soot body 9 is formed from the soot.
[0092] To rotate the substrate tube 1, the glass lathe 2 transmits a torque to the hollow spindles 2a, 2b. At the same time, an axially acting pressure F is generated by the compression spring 2c, which presses the two hollow spindles 3a, 3b against each other and ranges between 0.5 kN and 10 kN depending on the spring deflection from its rest length. The initial pressure setting is 1 kn and is applied to the pressure plates 4a, 4b, the buffer disks 5a, 5b and thus also to the substrate tube end faces 1a, 1b. This pressure F forms a frictional bond between the buffer disks 5a, 5b, which is sufficient to support the inherent weight of the substrate tube 1 and the weight of the soot body 9. The centering rings 7a, 7b, 7c are used only to prevent unexpected slippage and deflection of the substrate tube 1. A certain degree of axial guidance is provided by the interaction of the hollow spindles 3a, 3b with the centering support 6, which compensates for any radial offset or angular difference between the rotation axes of the hollow spindles 3a, 3b due to the existing mechanical play and avoids mechanical stresses.
[0093] The deposition method is stopped as soon as the soot body 9 reaches a predetermined outer diameter, which corresponds to the predetermined outer diameter of the hollow cylindrical quartz glass composite plus a margin of at least 1 mm depending on the density of the soot layer. When the soot density is about 30% (relative to the density of the quartz glass) and the target outer diameter of the quartz glass composite is 362 mm, the soot body outer diameter is, for example, about 520 mm.
[0094] After the deposition process, the soot body 9 is substantially barrel-shaped and extends on both sides to just short of the ends of the substrate tube 1. Protruding from the soot body 9 are SiO 2 The substrate tube section 1g, which is only lightly covered with soot, is approximately 100 mm long.
[0095] [Drying and vitrification process] The substrate tube 1 remains in the soot body 9. The composite (1;9) consisting of the substrate tube 1 and the soot body 9 is subjected to a dehydration treatment in a drying furnace in an inert gas atmosphere, a halogen-containing atmosphere or under vacuum. Here, the drying of the soot body 9 is carried out thermally by heating it to a temperature of about 1100°C in a nitrogen atmosphere. The dried SiO 2 By vitrifying the soot body under vacuum, a synthetic quartz glass having the following properties is obtained. Hydroxyl content: Approximately 200 ppm by weight Chlorine content: <0.2 ppm by weight Viscosity at 1350°C: 10.77 log(dPa·s).
[0096] The subsequent vitrification of the soot body 9 is carried out in a zone sintering furnace with the substrate tube longitudinal axis 1e oriented vertically, under vacuum or in an atmosphere of gases such as helium or hydrogen, which diffuse quickly in quartz glass and do not produce bubbles. FIG. 4 shows a schematic part of such a zone sintering furnace 40. The furnace chamber 41 surrounds a furnace interior 42 in which an annular heating element 43 and a holding device 44 are located. This device includes a carrier rod 45 made of fiber-reinforced carbon and connected at its lower end to a pedestal 46 made of graphite. The upper end of the carrier rod 45 is held by a movable gripper (not shown) so that it can be moved up and down. The carrier rod 45 extends through the annular opening of the heating element 43 and through a jacket tube 47 made of graphite standing on the pedestal 46. The jacket tube end faces are closed, except for the passage of the carrier rod 45. Compared to a jacket tube open on both sides, the mainly closed upper and lower sides 47a give the jacket tube 47 a higher shape rigidity against externally acting pressure.
[0097] During vitrification, the substrate tube 1 remains in the soot body 9. A holding device 44 holds the composite (1;9) consisting of the substrate tube 1 and the soot body 9, the weight of which is supported on a platform 46 by means of support rods 45. As shown diagrammatically in FIG. 5, the substrate tube 1 surrounds a jacket tube 47, the outer diameter of which is adapted to the inner diameter of the substrate tube 1 in such a way that the annular gap remaining during sintering is as small as possible, for example in the range of 1 mm to 10 mm, preferably less than 5 mm, taking into account the higher thermal expansion coefficient of the graphite jacket tube 47 compared to the quartz glass substrate tube.
[0098] During vitrification, the heating element 43 is heated to a temperature of about 1400 ° C and the carrier rod 45 is continuously pulled upwards so that the soot body 9 is vitrified from top to bottom. At this time, the composite (1; 9) shrinks onto the jacket tube 47, whereby its outer diameter defines the lower limit of the inner diameter of the vitrified tubular quartz glass composite. The substrate tube 1 consists of natural quartz glass, which at the sintering temperature has a higher viscosity than the synthetic quartz glass of the soot body 9. At a measurement temperature of 1350 ° C, according to Table 1, the viscosity difference corresponding to the difference between the common logarithms of the respective viscosity values is about 0.51 log (dPa·s) [11.28 log (dPa·s) - 10.77 log (dPa·s)].
[0099] The substrate tube 1 is thus relatively thermally stable and does not or only slightly deforms, which leads to a stabilization of the soot body 9 during vitrification, in particular preventing the risk that the soot body 9 will collapse during vitrification and form circumferential folds or expand its inner diameter, which would lead to rejects.
[0100] After cooling, a tubular composite of the substrate tube 1 and the glass layer is obtained with a thickness of about 41 mm, obtained by vitrifying the soot body 9. Although the synthetic quartz glass shrinks onto the inner graphite jacket tube 47, this glass can be easily removed after vitrification, since graphite has a significantly higher thermal expansion coefficient than quartz glass and therefore shrinks more on cooling.
[0101] The quartz glass of the substrate tube 1 can then be removed by mechanical processing, for example by drilling. After grinding and smoothing the outer wall, a hollow cylinder of quartz glass with an outer diameter of 360 mm and an inner diameter of 290 mm is obtained.
[0102] [Comparative Example] As explained above, due to its relatively high viscosity, the substrate tube 1 contributes to stabilizing the shape of the soot body 9 during vitrification.
[0103] To investigate the effect of the substrate tube 1 on the shape stabilization of the soot body 9, in a first comparative experiment, the substrate tube was removed before vitrification and only the soot body 9 was vitrified in the zone sintering furnace 40 starting from the top and working downwards. This caused the soot body 9 to collapse under its own weight and the vitrified area to come off the jacket tube 47, which leads to a local expansion of the inner diameter. The quartz glass tube produced in this way was unusable.
[0104] In further comparative experiments, a substrate tube made of synthetic quartz glass was used with the same dimensions as substrate tube 1, as specified in Table 1, No. 3. The viscosity of this quartz glass is lower than that of the quartz glass obtained by vitrification of soot body 9. As a result, with this composite, the jacket tube provides better adhesion to the vitrified soot body 9 and no extensive detachment of the vitrified material occurred. However, the weight of the vitrified upper region of the composite continued to increase, resulting in compression towards the end of the process, so that the quartz glass tube thus produced was also ultimately unusable.
[0105] In a further comparative experiment, a substrate tube made of synthetic quartz glass was used with the same dimensions as substrate tube 1, as specified in Table 1 under No. 4. The viscosity of this quartz glass corresponds to the viscosity of the quartz glass obtained by vitrification of soot body 9. However, here too, during sintering of the composite (1;9), compaction occurred towards the end of the process, so that the quartz glass tube produced in this way was also ultimately unusable.
[0106] [Suspension Vitrification] In order to counteract the effects of compression from the inherent weight, a vitrification method is often used in which the composite (1;9) is held at least temporarily in suspension during vitrification rather than standing constantly on a pedestal 46. This method is known for example from EP 0701975 B1 and is referred to here as "suspension vitrification" for short.
[0107] This ensures that the composite (1;9) remains suspended in the vitrification furnace from the start or that the holding of the composite (1;9) during the vitrification process can be switched from a standing state at the beginning of vitrification to a suspended holding as soon as the inevitable axial sintering shrinkage becomes significant. To achieve a suspended holding, measures can also be taken on the substrate tube before the external deposition method is carried out. This can be done, for example, by forming the substrate tube or by a forming process during the production of the substrate tube, such as by creating a constriction of the inner bore of the substrate tube when the substrate tube is pulled out of the melt or during the pulling process in which the mother tube is stretched to form the substrate tube. Alternatively or additionally, these measures are also preferably carried out "in situ" during vitrification.
[0108] A suitable measure for achieving suspended vitrification is to form a holding end of the substrate tube which serves to ensure that the composite (1;9) is vitrified at least temporarily in a vertically suspended state (not just standing). As a result of the at least temporary suspended state in addition to the effect of the thermally stable substrate tube 1 explained above, compression during vitrification of the soot body 9 is counteracted, the desired shape is maintained and rejects are avoided.
[0109] For the suspension of the composite (1;9), for example the substrate tube section 1g can be deformed to form a holding edge during vitrification of the soot body 9. A suitable method for producing a holding edge "in situ" is explained in more detail below with reference to Figures 6 to 10.
[0110] FIG. 6 shows a schematic diagram of a first method and device for forming the suspension "in situ". The composite (1;9) consisting of the substrate tube 1 and the soot body 9 is placed in the vitrification furnace 40 and is supported on a pedestal 46 by a carrier rod 45 and a jacket tube 47 with the soot body longitudinal axis 1e oriented vertically. An annular spacer 61 is placed on the upper end surface 47a of the jacket tube 47 and a cone 62 is placed in the shape of an inverted cup on the upper end surface of the substrate tube 9. The spacer 61 and the cone 62 are made of graphite. The cone 62 has an inner cone 62a that merges with a flat support surface 62b with a through opening 62c. In the initial state, the inner cone 62 adjoins the outer side of the upper part of the substrate tube section 1g. The carrier rod 45 extends through the through opening 62c and through the annular spacer 61.
[0111] The upper substrate tube section 1g is shaped to form a suspension during the vitrification process. The shaping process is shown diagrammatically in FIG. 7. The upper substrate tube section 1g is moved by the carrier rod 45 into the heating element 43, which is heated to the vitrification temperature sufficiently to soften it. Due to its weight, the cone 62 pushes the soft upper substrate tube section 1g inwards in the direction of the substrate tube longitudinal axis 1e. This brings the substrate tube section 1g into contact with the inner cone 62a and thereby deforms it to form the outer cone. The deformation process is stopped as soon as the spacer 61 comes into contact with the support surface 62b of the cone 62.
[0112] During further vitrification, the composite (1;9) is heated zone by zone starting from the top end, which causes the composite (1;9) to continuously collapse onto the graphite jacket tube 47 and to shrink in length again. The sintering shrinkage forces are now strong enough that the length of the substrate tube 1 also shortens. However, the shrinkage in length is small.
[0113] In the first vitrification stage, the composite (1;9) stands on the pedestal 46. Figure 8 shows the second vitrification stage in a schematic way. During this, the former substrate tube part 1g, formed into an external cone, leaves the heating area of the heating element 43, cools and solidifies. It adjoins the upper side of the jacket tube 47a on the inside and serves as a suspension 63 for the composite (1;9). As a result of the contraction in length, this composite is lifted from the pedestal 46 and a narrow gap 48 is formed, which allows further "suspension vitrification". This counteracts the collapse of the soot body 9 and the substrate tube 47, due to its higher viscosity, further stabilizes the shape of the obtained tubular quartz glass composite.
[0114] FIG. 9 shows a schematic diagram of a second method and apparatus for forming the suspension in situ, i.e. in one operation with the vitrification of the composite (1;9) consisting of the substrate tube 1 and the soot body 9. It is placed in the vitrification furnace 40 and is supported on a pedestal 46 by a carrier rod 45 and a jacket tube 47 with the soot tube longitudinal axis 1e oriented vertically. A circular ring 91 is placed on the upper end surface 47a of the jacket tube 47 and consists of two or more separate sector plates 91a, 91b arranged so as to be radially movable adjacent to the circular ring central opening 91b. A cone 92 made of graphite and having a conical shaft 92a and a conical head 92b with a flat base protrudes from above into the central opening 91b. The circular ring 91 and the cone 92 are made of graphite. The outer diameter of the circular ring 91 approximately corresponds to the inner diameter of the substrate tube 1 and is placed against the inner wall of the upper part 1g of the substrate tube. The diameter of the conical shaft 92a is designed so that it is initially inserted approximately halfway into the central opening 91b.
[0115] During further vitrification of the composite (1;9), the bulge 93 enters the area above the heating element 43 and cools and solidifies. As explained above for the first method, the composite (1,9) is heated zone by zone, starting from the top end. During the first vitrification stage the composite (1;9) stands on the pedestal 46, while during the second vitrification stage the bulge 93 serves as a holder for "suspended vitrification". The sector plate 91a protrudes from the inside into the bulge 93 where it is fixed vertically together with the substrate tube 1.
[0116] The length and inner diameter of the quartz glass composite thus obtained are predefined by the substrate tube 1. The original soot body forms a layer of transparent synthetic quartz glass with a layer thickness of 41 mm. After removal of the quartz glass material of the substrate tube 1 and grinding and smoothing of the outer wall, a hollow cylinder of quartz glass is obtained with an outer diameter of 360 mm and an inner diameter of 290 mm. From this, etching rings for single-wafer plasma etching chambers or pressure vessels for use in the chemical industry can be cut.
[0117] For the manufacture of etching rings and pressure vessels, composites are preferably used that have an outer wall region with an inner diameter at least 1 mm smaller than the target inner diameter, which can be set by mechanical or chemical machining of the composite inner bore.
[0118] In the following, further exemplary embodiments for realizing a holding end for suspended vitrification of the composite (21,9) are described with reference to Figs. 2 and 3 and Figs. 11 to 13.
[0119] [Soot Deposition Process] The soot deposition process is carried out as explained above with reference to figure 1. Figure 11 shows in longitudinal section a substrate tube 21 used in this process. A prefabricated constriction 26 is provided in the end region 21a. As can be seen in figure 2, the soot body 9 is made to completely cover the constriction 26. However, this measure is not necessary and the constriction may also be completely outside the soot body 9.
[0120] The deposition process is stopped as soon as the soot body 9 reaches a desired outer diameter, which is approximately 520 mm when the soot density is 30% (relative to the density of the quartz glass) and the target outer diameter of the quartz glass composite is 362 mm.
[0121] The composite (21;9) present after the soot deposition process is subjected to a dehydration treatment at a temperature of 1200 °C in a chlorine-containing atmosphere. The resulting dry SiO 2By vitrifying the soot body under vacuum, a synthetic quartz glass having the following properties is obtained. Hydroxyl content: <0.2 ppm by weight Chlorine content: Approximately 1,000 ppm by weight Viscosity at 1350℃: 10.64 log(dPa·s)
[0122] The composite (21;9) is then vitrified under vacuum in a zone sintering furnace 40. FIG. 12 shows the composite (21;9) placed in the zone sintering furnace 40. During vitrification, the heating element 43 is heated to a vitrification temperature of about 1400° C. and the carrier rod 45 is continuously pulled upwards so that the soot body 9 is vitrified from top to bottom. At this time, the composite (21;9) shrinks onto the graphite jacket tube 47, whereby its outer diameter defines the lower limit of the inner diameter of the vitrified quartz glass composite. The substrate tube 21 is made of quartz glass, which at the vitrification temperature has a higher viscosity than the quartz glass of the soot body 9, and therefore does not or only slightly deforms, stabilizing the soot body 9 during vitrification. In particular, the risk of the compressed soot body 9 being compressed during vitrification, of circumferential folds forming or of the inner diameter widening is suppressed.
[0123] At the stage of the method shown, the vitrification process has already progressed and some shrinkage of the soot body 9 has already occurred. This means that the transition from the first vitrification stage of the standing composite (21;9) to "suspended vitrification" is already complete. Due to the shrinkage of the soot body 9, the length of the substrate tube 21 has also been slightly shortened and it has already been lifted somewhat from the pedestal 46, forming a gap 98.
[0124] Alternatively, the composite (21;9) is initially held suspended in the zone sintering furnace by the already-existing constriction 26 adjacent the upper edge of the graphite jacketed tube 47 prior to the soot deposition process.
[0125] After cooling, the result of vitrification of the soot body 9 is a composite 100 (FIG. 13) consisting of the substrate tube 21 and a glass layer 9a having a thickness of about 41 mm.
[0126] In the comparative experiment, a substrate tube made of synthetic quartz glass having the same dimensions as the substrate tube 21 was used, as specified in No. 3 of Table 1. The viscosity of this quartz glass is higher than the viscosity of quartz glass obtained by vitrifying the soot body 9. More precisely, the common logarithm of the viscosity of this quartz glass at the measurement temperature of 1350°C is 0.13 log (dPa s) higher than the common logarithm of the viscosity of quartz glass obtained by vitrifying the soot body 9.
[0127] However, this viscosity difference was found to be too small to provide sufficient stability for large volume, heavy substrate tubes when sintering the composite.
[0128] Figure 13 shows a cross-sectional view of the composite 100 obtained after vitrification along the line A'-A'' drawn in Figure 2. Shown is the substrate tube 1 with the through hole 1f, the diameter constriction 26 and the layer 9a of synthetic quartz glass obtained after vitrification.
[0129] After removal of the quartz glass material of the substrate tube 21 and grinding and smoothing of the outer wall, a hollow cylinder of quartz glass with an outer diameter of 360 mm and an inner diameter of 290 mm is obtained. Etching rings for holding semiconductor wafers in single-wafer plasma etching chambers or industrial pressure vessels with corresponding inner and outer diameter values, or with larger inner and smaller outer diameter values, can be cut therefrom.
Claims
1. A method for producing a tubular quartz glass composite in an external deposition process, comprising the steps of: (a) providing a sub-straight tube having a through opening extending coaxially with and continuous with a longitudinal axis of the sub-straight tube, a sub-straight tube outer diameter, a sub-straight tube inner diameter, a sub-straight tube wall thickness, a sub-straight tube outer surface, and a sub-straight tube inner surface; (b) rotating the substrate tube about a rotation axis extending coaxially or parallel to a longitudinal axis of the substrate tube; (c) depositing SiO.sub.2 on the outer surface of the substrate tube by at least one deposition burner. 2 The substrate tube and SiO 2 forming a composite (1 / 9; 21 / 9) from the soot body; (d) sintering the composite (1 / 9; 21 / 9) by heating at a sintering temperature to form the tubular quartz glass composite (100); Including, A method comprising providing a substrate tube at least partially made of quartz glass having a first quartz glass property, the soot body being made of quartz glass having a second quartz glass property, the first quartz glass property having a material-specific viscosity at a sintering temperature that is higher than the material-specific viscosity of the second quartz glass property.
2. 2. The method according to claim 1, characterized in that the common logarithm of the viscosity of the first quartz glass property at a measurement temperature of 1350 ° C is at least 0.25 log (dPa s), preferably at least 0.4 log (dPa s), particularly preferably at least 0.6 log (dPa s) higher than that of the second quartz glass property.
3. 3. The method according to claim 1, wherein the quartz glass of the first quartz glass property has an aluminium oxide content that is at least 5 ppm by weight, preferably at least 10 ppm by weight, higher than the aluminium oxide content of the quartz glass of the second quartz glass property.
4. 4. The method according to claim 1, wherein the quartz glass of the first quartz glass quality has a hydroxyl group content of less than 30 ppm by weight, preferably a hydroxyl group content of less than 20 ppm by weight.
5. 5. The method according to claim 1, wherein the quartz glass of the first quartz glass quality is melted from a naturally occurring source material.
6. Method according to one or more of the preceding claims, characterized in that the substrate tube has a wall thickness in the range of 1.5mm to 10mm, preferably in the range of 4 to 8mm.
7. 7. The method according to one or more of the preceding claims, characterized in that the soot body is substantially cylindrical and the wall thickness is such that after sintering of the composite a glass layer is obtained with a layer thickness in the range of 25 mm to 100 mm, preferably in the range of 30 mm to 60 mm.
8. A tubular composite made of quartz glass, having a tube wall having a length of at least 1000 mm and an inner diameter of at least 250 mm, the unprocessed wall having an inner wall region and an outer wall region, the inner wall region at least partially made of quartz glass of a first quartz glass property and the outer wall region made of quartz glass of a second quartz glass property, the viscosity of the first quartz glass property being higher than the viscosity of the second quartz glass property at a measurement temperature of 1350°C.
9. 9. The composite according to claim 8, characterized in that the common logarithm of the viscosity of the first quartz glass property at a measurement temperature of 1350 ° C is at least 0.25 log (dPa s), preferably at least 0.4 log (dPa s), particularly preferably at least 0.6 log (dPa s) higher than that of the quartz glass of the second quartz glass property.
10. 10. The composite according to claim 8 or 9, characterized in that the quartz glass of the first quartz glass property has an aluminium oxide content that is at least 5 ppm by weight, preferably at least 10 ppm by weight, higher than the aluminium oxide content of the quartz glass of the second quartz glass property.
11. 11. A composite according to one or more of claims 8 to 10, characterized in that the quartz glass of the first quartz glass nature is melted from a naturally occurring source.
12. 12. Composite according to one or more of claims 8 to 11, characterized in that the inner wall region of the first quality quartz glass has a wall thickness in the range of 1.5 mm to 10 mm, preferably in the range of 4 to 8 mm.
13. A composite according to one or more of claims 8 to 12, characterized in that the outer wall region has a wall thickness in the range of 25mm to 100mm, preferably in the range of 30mm to 60mm.
14. 14. Use of a tubular composite according to one or more of claims 9 to 13 for producing an etching ring or a pressure vessel for semiconductor manufacturing, characterized in that the inner wall region is removed to produce a hollow cylinder of quartz glass, which is processed to form the etching ring or the pressure vessel.
15. 15. The method of claim 14, wherein the etching ring or the pressure vessel has a predetermined target inner diameter, and a composite having an outer wall region with an inner diameter at least 1 mm smaller than the target inner diameter is used to manufacture the etching ring or the pressure vessel.